Imported leishmaniasis in Sweden 1993–2016. Issue 10 (31st May 2018) - Söbirk, S. K.; Inghammar, M.; Collin, M.; Davidsson, L.
Abstract: In Sweden, leishmaniasis is an imported disease and its epidemiology and incidence were not known until now. We conducted a retrospective, nationwide, epidemiological study from 1993 to 2016. Probable cases were patients with leishmaniasis diagnoses reported to the Swedish Patient registry, collecting data on admitted patients in Swedish healthcare since 1993 and out-patient visits since 2001. Confirmed cases were those with a laboratory test positive for leishmaniasis during 1993–2016. 299 probable cases and 182 confirmed cases were identified. Annual incidence ranged from 0.023 to 0.35 per 100 000 with a rapid increase in the last 4 years. Of 182 laboratory-verified cases, 96 were diagnosed from 2013 to 2016, and in this group, almost half of the patients were children under 18 years. Patients presented in different healthcare settings in all regions of Sweden. Cutaneous leishmaniasis was the most common clinical manifestation and the majority of infections were acquired in Asia including the Middle East, specifically Syria and Afghanistan. Leishmania tropica was responsible for the majority of cases (42%). A combination of laboratory methods increased the sensitivity of diagnosis among confirmed cases. In 2016, one-tenth of the Swedish population were born in Leishmania -endemic countries and many Swedes travel to these countries for work or vacation. Swedish residents who have spent time in Leishmania -endemic areas, could be at risk of developing disease some time during their lives. Increased awareness and knowledge are needed for correct diagnosis and management of leishmaniasis in Sweden.